STRATEGIES TO INCREASE VOTER PARTICIPATION IN THE MIDDLE OF THE COVID-19 PANDEMIC AT THE SIMULAR ELECTIONS IN BONE BOLANGO DISTRICT - Djau, Ramli Ondang; Abdussamad, Zuhcri (Universitas Negeri Gorontalo, 2022)
Voter Participation determines the legitimacy of a stage and process of holding the 2020 Simultaneous Pilkada, it is very risky if the voter participation rate decreases or even does not reach the national target. The pandemic condition opens up great potential for the decline in the participation rate. This study aims to find out the strategy carried out by the General Election Commission of Bone Bolango Regency in an effort to increase voter participation in the midst of the Covid 19 pandemic, what steps and strategies were chosen and of course what instruments were used to achieve voter turnout in the midst of the pandemic. The method used in this research is qualitative, with data collection through three events, namely, observation. interviews, and documentation. The results of this study indicate that,